Nonlinear and Heterogeneous Effect of Digitalization on Foreign Direct Investment: Evidence from Developing Countries - Ho, Thi Lam; Ngoc, Le Hong; Ho, Thu Hoai (Ital Publication, 2025)
This study aims to clarify whether digitalization has a nonlinear and heterogeneous effect on foreign direct investment (FDI) inflows in developing countries. We employ data from the period 2002–2023 and apply various econometric methods, including System Generalized Method of Moments (S-GMM), Dynamic Panel Threshold Regression (DTPR), and Method of Moment Quantile Regression (MMQR), to address the research question. The findings report an inverted U-shaped relationship between digitalization and FDI. Specifically, the effect of digitalization on FDI changes across different levels of digitalization. Initially, digitalization positively affects FDI, but beyond a certain threshold, its impact turns negative. This indicates that the benefits of digitalization for FDI are not unlimited but may be constrained by the risks and costs associated with excessive digital infrastructure expansion. Additionally, the MMQR analysis shows a heterogeneous effect of digitalization on FDI. Digitalization has a stronger impact on FDI at lower quantiles. However, as a country's development level increases, the effectiveness of digitalization in attracting FDI gradually diminishes. Policymakers need to identify and maintain an optimal level of digitalization to promote FDI. This requires not only investment in digital infrastructure but also in supporting factors such as improved governance quality and the development of legal frameworks to ensure a stable and conducive economic environment for FDI. Moreover, flexible policies tailored to different country or regional groups are necessary to maximize the benefits of digitalization without triggering negative impacts on long-term economic development.